EKONOMI HIJAU: PENGEMBANGAN EKONOMI DAN DESAIN KREATIF DAUR ULANG PLASTIK PADA PERKUMPULAN AKSARA YOGYAKARTA - Subanar, Gregorius Budi; Anurogo, Baskoro Latu; Budisusila, Antonius; Sitorus, Gabriella Angela; Nugroho, Dhaniel Aryo; Papur, Maria Griselda Delwella; Saribu, Ester Amelia Tambun (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program, conducted by the Institute for Research and Community Service at Sanata Dharma University in collaboration with Aksara Association, aims to strengthen the economic independence of local members by transforming plastic waste into value-added products. Key activities include outreach, technical training, production mentoring, craft-design development, and digital marketing. These initiatives are designed to enhance participants’ skills in creative business management, design innovation, recycling techniques, and online marketing. The program was evaluated using quantitative and qualitative methods. Quantitative assessment relied on participant satisfaction surveys and comparisons between targets and achievements, while qualitative assessment used mentoring records and focus group discussions to examine process quality and collaboration. Results show strong participant enthusiasm, improved knowledge and skills in plastic waste processing, and the successful production of Plastic Wood Composite (PWC) and craft products. Digital marketing also expanded audience reach and boosted sales. The program highlights the value of cross-sector collaboration and sustainable design for strengthening the local green economy.